(untitled) (Global Journal of Human-Social Science, 2016)
This paper probes French-Western manipulative policies and activities in Mali within the framework of critical theory of international relations, while at the same time, examining globalisation as "colonialism" by other means. It then goes on to assess the role played by France in both the cause and containment of the Malian crisis and the implications of the intervention on the national security and overall development of Mali. The paper, therefore, argues that French interest in Mali, is overwhelmingly high and has great consequences on the leadership struggle and governmental policies of the country. Factors that favoured the rise of the conflict are MNLA’s long-term goal of establishing a Tuareg State in self-determination coupled with Mali’s extreme economic and political dependence on outside assistance. Findings have revealed that France, is part of a wider design and struggle, within the Western World and particularly, within the foreign policy controlling group in Washington. Finally, the activities of France in the management of the conflict are widely observed as devoid of altruism.